Creating Policy Participation of Health Behavior for Reduce Cancer, Hypertension and Cardiovascular Disease in Maelan Subdistrict, Li District, Lamphun Province - Thammakawinwong, Nathakrid (Journal of The Royal Thai Army Nurses, 2020)
Creating policy participation of health behavior in subdistrict for reduce cancer, hypertension and cardiovascular disease in Maelan Subdistrict, Li District Lamphun Province with the objectives were 1) to study participation in creating policy participation 2) to study health behavior 3) Creating policy participation of health behavior. Research design to participatory action research. Creating policy participation by planning, action, monitoring, evaluation process. The sample size were 60 by purposive sampling. Analyze data by percentage, Mean and standard deviation, analyze the inductive analysis by Thematic analysis and Typology and Taxonomy. Result Participation of creating policy participation were average 3.72, Comparing before and after creating policy participation was a significant at the level .05 Health behavior were average 3.28. Comparing before and after creating policy participation was a significant at the level 0.05. Creating policy participation consists of 5 component : 1) Nutrition were focus on catering buffet in the traditional village. 2) Exercise were focus on sports of community and exercise 3 times per week for at least 30 minutes 3) Alcohol were not alcoholic in the traditional village 4) Smoking were focus on non-smoking in house and communicate and persuade people in community non-smoking with law enforcement 5) Stress were focus on relaxation activities stress and counseling